Given the Bateman equations $$ N_1(t)=N_1(0)e^{-\lambda_1 t} \\ N_2(t)=N_1(0) \frac{\lambda_1}{\lambda_2-\lambda_1} (e^{-\lambda_1 t}-e^{-\lambda_2 t}) $$

And given that the activities $A_1$ and $A_2$ are related by $A_2=A_1$ at $t=t_A$ and $A_2=3A_1$ at $t=2t_A$, I'm asked to compute $\lambda_1$ and $\lambda_2$ in terms of $t_A$.

I can compute the activity equations by

$$ A_1(t)=-\frac{d N_1}{dt} = \lambda_1 N_1(0)e^{-\lambda_1 t} \\ A_2(t)=-\frac{d N_2}{dt}=N_1(0) \frac{\lambda_1}{\lambda_2-\lambda_1} (\lambda_1 e^{-\lambda_1 t}- \lambda_2 e^{-\lambda_2 t}) $$

And so using these conditions leads to the equations

$$ \lambda_1 N_1(0)e^{-\lambda_1 t_A} = N_1(0) \frac{\lambda_1}{\lambda_2-\lambda_1} (\lambda_1 e^{-\lambda_1 t_A}- \lambda_2 e^{-\lambda_2 t_A}) \\ 3 \lambda_1 N_1(0)e^{-\lambda_1 2 t_A} = N_1(0) \frac{\lambda_1}{\lambda_2-\lambda_1} (\lambda_1 e^{-\lambda_1 2 t_A}- \lambda_2 e^{-\lambda_2 2 t_A}) $$

However, these equations are transcendental, and I cannot solve for $\lambda_1$ & $\lambda_2$ explicitly.

I was wondering, how would I avoid this problem? Are there ways of removing the transcendental nature of the equations? Are there simplifying assumptions that can be made to simplify the equations? How would I solve for $\lambda_1$ & $\lambda_2$ ?

  • $\begingroup$ Why not solve for lambdas numerically? $\endgroup$ Apr 26, 2020 at 12:36
  • $\begingroup$ It is possible to solve for the lambdas exactly, even if it is a bit heavy. I will detail the calculations in an answer. $\endgroup$ Apr 26, 2020 at 14:24

1 Answer 1


First, I believe you've made a mistake in the expression of $A_2$. Because of the minus sign in front, it should read:

$$A_2(t) = N_1(0) \frac{\lambda_1}{\lambda_2-\lambda_1} \left(\lambda_1 e^{-\lambda_1 t} - \lambda_2 e^{-\lambda_2 t} \right)$$

Note that the expression you got for $N_2$ is only valid for $\lambda_2 \neq \lambda_1$.

So the first condition can be written instead as:

$$\lambda_1 N_1(0) e^{-\lambda_1 t_A} = N_1(0) \frac{\lambda_1}{\lambda_2-\lambda_1} \left(\lambda_1 e^{-\lambda_1 t_A} - \lambda_2 e^{-\lambda_2 t_A} \right)$$

Simplifying by the common factors, and with a bit of algebra, this can be aranged into the following equation:

\begin{align} &\frac{\lambda_2}{\lambda_2-\lambda_1} e^{-\lambda_2 t_A} = \left(\frac{\lambda_1}{\lambda_2 - \lambda_1} -1 \right) e^{-\lambda_1 t_A}\\ \Leftrightarrow \quad &\frac{\lambda_2}{\lambda_2-\lambda_1} e^{-\lambda_2 t_A} = \frac{2\lambda_1 - \lambda_2}{\lambda_2 - \lambda_1} e^{-\lambda_1 t_A} \\ \Leftrightarrow \quad &\frac{\lambda_2}{2\lambda_1-\lambda_2} = e^{(\lambda_2-\lambda_1) t_A} \\ \end{align}

Similarly, using the second equation, we find:

$$\frac{\lambda_2}{4 \lambda_1 - 3\lambda_2} = e^{2(\lambda_2-\lambda_1) t_A}$$

But the RHS here is just the square of the first RHS, meaning that we must have:

\begin{align} &\left(\frac{\lambda_2}{2\lambda_1-\lambda_2} \right)^2 = \frac{\lambda_2}{4 \lambda_1 - 3\lambda_2} \quad \quad \quad (1)\\ \Leftrightarrow \quad &\lambda_2 (4\lambda_1 - 3\lambda_2) = (2 \lambda_1 - \lambda_2)^2 \\ \Leftrightarrow \quad &4 \lambda_2^2 - 8 \lambda_1 \lambda_2 + 4 \lambda_1^2 = 0 \\ \Leftrightarrow \quad &4 (\lambda_2 - \lambda_1)^2 = 0 \\ \Leftrightarrow \quad &\lambda_2 = \lambda_1 \end{align}

This is contradictory with the assumption that $\lambda_2 \neq \lambda_1$ to derive $N_2(t)$. In fact, if $\lambda_2 = \lambda_1 = \lambda$, it can be shown that the solutions to the Bateman equations are:

\begin{align} N_1(t) &= N_1(0) e^{-\lambda t} \\ N_2(t) &= N_1(0) \lambda t e^{-\lambda t} \end{align}

with the corresponding activities:

\begin{align} A_1(t) &= N_1(0) \lambda e^{-\lambda t} \\ A_2(t) &= N_1(0) \lambda (\lambda t - 1) e^{-\lambda t} \end{align}

Under these conditions, it can be shown easily that $A_1(t_A) = A_2(t_A)$ iff $\lambda = 2/t_A$. You can check that with this choice of $\lambda$, the second condition is automatically fulfilled and that $A_2(2 t_A) = 3 A_1(2 t_A)$, as expected.

Note that this particuliar solution with a linear dependency in front of the exponential for $N_2(t)$ only occurs because $\lambda_2 = \lambda_1$. If we would have chosen pretty much any other conditions, we would have found $\lambda_2 \neq \lambda_1$ by solving the equation equivalent to $(1)$. After finding the relative values of $\lambda_2$ and $\lambda_1$, you can find their absolute value (in terms of $1/t_A$) by injecting the equality between $\lambda_1$ and $\lambda_2$ into the first equation for instance.

Numerical check:

as it is always nice to check this kind of lengthy calculations, I have implemented numerically the Bateman equations in their differential form into Python. You can check that for $\lambda_1 = \lambda_2 = 2/t_A$ this yields the correct ratio of activities at $t = t_A$ and $t = 2t_A$.

general plot


Please find below the Python script used to generate these pictures:

import numpy as np

tA = 1.0 #arbitraty units
lambda_1 = 2/tA
lambda_2 = 1.*lambda_1
N0_1 = 1 #also arbitrary
N0_2 = 0 #assuming no atoms 2 at the beginning
t_max = 4*tA
N_steps = 1000
dt = t_max/N_steps

N_steps_tA = N_steps//4 #number of steps corresponding to t=tA
N_steps_2tA = 2*N_steps_tA #number of steps corresponding to t=2tA

N1 = np.zeros(N_steps+1)
N1[0] = N0_1
N2 = np.zeros(N_steps+1)
N2[0] = N0_2

for i in range(1, N_steps+1):
    N1[i] = (N1[i-1] - lambda_1*dt*N1[i-1]/2)/(1 + lambda_1*dt/2) #half step euler method
    N2[i] = (N2[i-1] - lambda_2*dt*N2[i-1]/2 + N1[i-1] - N1[i])/(1 + lambda_1*dt/2)

def A1(N):
    return -(N1[N+1]-N1[N-1])/(2*dt)

def A2(N):
    return -(N2[N+1]-N2[N-1])/(2*dt)

print(A1(N=N_steps_tA), A2(N=N_steps_tA))
print(3*A1(N=N_steps_2tA), A2(N=N_steps_2tA))
  • $\begingroup$ You're right about the incorrect A2 equation - I'll update it there. $\endgroup$
    – David
    Apr 26, 2020 at 20:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.